Evaluating the effects of dexmedetomidine compared to propofol as adjunctive therapy in patients with alcohol withdrawal - Lizotte RJ; Kappes JA; Bartel BJ; Hayes KM; Lesselyoung VL (Dove Medical Press, 2014)
Riley J Lizotte,1 John A Kappes,2 Billie J Bartel,2 Katie M Hayes,1 Veronica L Lesselyoung1 1Pharmacy Department, Rapid City Regional Hospital, Rapid City, SD, USA; 2Pharmacy Practice, South Dakota State University, Brookings, SD, USA Background: In severe alcohol withdrawal (AW), benzodiazepines may be inadequate to control symptoms. In many situations, benzodiazepine dosing escalates despite no additional efficacy and introduces potential toxicities. Severe cases of AW may require additional agents to control symptoms. Case reports and studies have shown benefits with dexmedetomidine and propofol in severe AW, but these agents have not been compared with one another. This study compares the effects of dexmedetomidine and propofol on benzodiazepine and haloperidol utilization in patients with AW. Methods: A retrospective chart review was completed on 41 patients with AW who received adjunctive dexmedetomidine or propofol. The primary objective was to compare benzodiazepine and haloperidol utilization before and after initiation of dexmedetomidine or propofol. Secondary measures included AW and sedation scoring, analgesic use, intensive care unit length of stay, rates of intubation, and adverse events. Results: Among the dexmedetomidine and propofol groups, significant reductions in benzodiazepine (P≤0.0001 and P=0.043, respectively) and haloperidol (P≤0.0001 and P=0.026, respectively) requirements were observed. These reductions were comparable between groups (P=0.933 and P=0.465, respectively). A trend toward decreased intensive care unit length of stay in the dexmedetomidine group (123.6 hours vs 156.5 hours; P=0.125) was seen. Rates of intubation (14.7% vs 100%) and time of intubation (19.9 hours vs 97.6 hours; P=0.002) were less in the dexmedetomidine group. Incidence of hypotension was 17.6% in the dexmedetomidine group vs 28.5% in the propofol group. Incidence of bradycardia was 17.6% in the dexmedetomidine group vs 0% in the propofol group. No differences were observed in other secondary outcomes. Conclusion: In patients with severe AW who require sedation, both dexmedetomidine and propofol have unique and advantageous properties. Both agents appear to have equivalent efficacy in reducing AW-related symptoms and benzodiazepine and haloperidol requirements. These results should be validated in a larger, prospective trial. Keywords: dexmedetomidine, propofol, benzodiazepines, alcohol, withdrawal